2013
DOI: 10.1088/0004-637x/772/2/103
|View full text |Cite
|
Sign up to set email alerts
|

COMPLETE INFRARED SPECTRAL ENERGY DISTRIBUTIONS OF MILLIMETER DETECTED QUASARS ATz> 5

Abstract: We present Herschel far-infrared (FIR) photometry of eleven quasars at redshift z > 5 that have previously been detected at 1.2 mm. We perform full spectral energy distribution (SED) fits over the wavelength range λ rest ∼ 0.1-400 µm for those objects with good Herschel detections. These fits reveal the need for an additional far-infrared (FIR) component besides the emission from a dusty AGNpowered torus. This additional FIR component has temperatures of T FIR ∼ 40-60 K with luminosities of L 8−1000µm ∼ 10 13 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
174
5
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(196 citation statements)
references
References 57 publications
15
174
5
2
Order By: Relevance
“…The only requirement was that the measured pixels should have a total integration time at least 0.75 times the integration time of that of the source of interest in order to exclude the noisy map edges (e.g. Leipski et al 2013). The 1σ photometric uncertainty of the map is taken to be the 1σ value of the Gaussian fitted to the flux densities measured in these 500 random positions.…”
Section: Pacsmentioning
confidence: 99%
“…The only requirement was that the measured pixels should have a total integration time at least 0.75 times the integration time of that of the source of interest in order to exclude the noisy map edges (e.g. Leipski et al 2013). The 1σ photometric uncertainty of the map is taken to be the 1σ value of the Gaussian fitted to the flux densities measured in these 500 random positions.…”
Section: Pacsmentioning
confidence: 99%
“…For instance, Ade et al (2011) gave the median value of β for our Galaxy as 1.8; Smith et al (2012) found that β varies from 1.7 to 2.5 in the Andromeda Galaxy using Herschel data. In order to compare FIR temperature with the literature, we fix the β value to 1.6 as suggested in Leipski et al (2013). The free parameters of the FIR dust component are temperature and scale.…”
Section: Extra Dust Componentmentioning
confidence: 99%
“…Yet the typical dust temperature at ultra-luminous infrared galaxies (ULIRGs) can be as low as 25-35 K (Hwang et al 2010). Thus, the FIR dust temperature is allowed to vary from 10 to 60 K. The initial temperature is set to be 44 K, the mean FIR dust temperature of the high-z quasars (Beelen et al 2006;Leipski et al 2013). To achieve a reliable temperature, the FIR data should be sampled around the peak of the SED at FIR.…”
Section: Fir Dust Temperaturementioning
confidence: 99%
See 2 more Smart Citations